Jebakan ‘Harga Murah Semu’ Layanan Daring Pengantar Makanan Go-Food dan Grab Food - Putra Aditya Lapalelo (LPPM Stikosa - AWS, 2022)
Delivery service applications such as Gojek and Grab in recent years have become part of the lives of urban people, becoming one of the instruments to fulfill the needs of urban consumers who are called